The use of indigenous bacterial community as inoculant for plant growth promotion in soybean cultivation. Issue 1 (2nd January 2023) - May, Andre; Coelho, Luciana Fontes; Pedrinho, Alexandre; Batista, Bruna Durante; Mendes, Lucas William; Mendes, Rodrigo; Morandi, Marcelo Augusto Boechat; Barth, Gabriel; Viana, Ronaldo Silva; Vilela, Elke Simoni Dias
ABSTRACT: We characterized the bacterial community in shoot and rhizosphere of healthy adult soybean plants grown in two differentially managed soils. Then, these communities were transplanted to seeds to assess their effect on seedling development. The bacterial communities of inoculated soybean seedlings were assessed through 16S rRNA amplicon sequencing and seedlings' growth was measured. The diversity in the bacterial consortium inoculum prepared from the rhizosphere was higher than those from the shoot. However, the application of bacterial consortium in seedling had no influence on diversity. The resulting bacterial community of seedlings inoculated with bacterial consortium presented an enrichment of specific plant growth-promoting groups, such as Gammaproteobacteria ( Enterobacter, Pseudomonas, and Xanthomonas ). The predicted potential functions showed an increased abundance of functions related to plant protection and nutrition. The application of bacterial consortium from the shoot of soybean plants grown in the soil with a previous history of soybean cultivation increased the seedling radicle length, hypocotyl length, and total dry weight by 44%, 30%, and 29%, respectively. Our study showed that selecting a consortium of indigenous microbes as inoculants is a potential approach to enhance the use and impacts of plant beneficial microorganisms on plant growth and possibly productivity.